2013
DOI: 10.1002/2013jg002296
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bacterial metabolic activity by dissolved organic carbon and viruses

Abstract: [1] The regulation of bacterial metabolic activity by viruses and dissolved organic carbon (DOC) was examined using natural microbial communities in three treatments (active viruses, inactive viruses, and virus free) at two contrasting coastal sites (pristine vs. eutrophic) with substantial differences in environmental conditions during the wet and dry seasons. Our results showed that net growth rates and production of bacterioplankton were reduced primarily by viruses via repressing metabolically active bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…The cell-specific bacterial respiration increased along the inshore-offshore transect except for Transect C, with the lowest in the eutrophic waters (i.e., Stn A1). It has been documented that the cell-specific bacterial respiration increased with environmental hostility in other studies (Baltar et al, 2015;Xu et al, 2013). At pristine stations with little influence of the river plume, cell-specific bacterial respiration was relatively high, likely since a large fraction of carbon is channeled to the adenosine 5 0 -triphosphate synthesis for maintenance rather than cell division (del Giorgio et al, 2011) under environmentally hostile conditions.…”
Section: 1029/2018jc014277mentioning
confidence: 88%
See 1 more Smart Citation
“…The cell-specific bacterial respiration increased along the inshore-offshore transect except for Transect C, with the lowest in the eutrophic waters (i.e., Stn A1). It has been documented that the cell-specific bacterial respiration increased with environmental hostility in other studies (Baltar et al, 2015;Xu et al, 2013). At pristine stations with little influence of the river plume, cell-specific bacterial respiration was relatively high, likely since a large fraction of carbon is channeled to the adenosine 5 0 -triphosphate synthesis for maintenance rather than cell division (del Giorgio et al, 2011) under environmentally hostile conditions.…”
Section: 1029/2018jc014277mentioning
confidence: 88%
“…The cell‐specific bacterioplankton production in this study was in agreement with the range reported for other coastal transition zone regions (Baltar et al, ). The increment in the cell‐specific bacterial production is tied to an increase in the proportion of the high nucleic acid bacteria in bacterial community (Xu et al, ). Bacterial production was significantly correlated with bacterial abundance (Figure a and Table ) indicating that the enhancement of bacterial production derived from not only increased bacterial abundance but also enhanced cell‐specific bacterial production.…”
Section: Discussionmentioning
confidence: 99%
“…5B). As HNA prokaryotes appear to have higher cell-specific leucine incorporation rates than LNA prokaryotes (39,41) and tend to be more susceptible to viral infection than LNA prokaryotes (42)(43)(44), the low LF eCFs could also be related to high cell-specific leucine incorporation rates along with a low net biomass increase of this bacterial functional group during the incubations. As grazing was minimized by prefiltration, we hypothesize that other factors, such as viral lysis or apoptosis, could be responsible for low net biomass accumulation during our incubations.…”
Section: Discussionmentioning
confidence: 99%
“…Today the roles of viruses are still a recurrent topic and the study of the microbial loop is far from exhausted (Middelboe et al, 2003;Sandaa, 2008;Ory et al, 2010;Yau et al, 2011;Magiopoulos and Pitta, 2012;Shelford et al, 2012;Xu et al, 2013;Brum et al, 2014;Hasumi and Nagata, 2014;Stock et al, 2014;Liu et al, 2015). Still, viruses are sometimes neglected (e.g., Follows and Dutkiewicz, 2010;Salihoglu et al, 2013), and only a few attempts have been made to model the details of bacterial and phytoplankton viral-induced cell lysis.…”
Section: Current State Of Modelingmentioning
confidence: 99%